Method for obtaining recombinant antibodies produced by a cell line transduced with recombinant adenoviruses - E. S. Sedova; D. N. Shcherbinin; A. S. Bandelyuk; L. V. Verkhovskaya; N. Yu. Viskova; E. D. Avdonina; V. V. Prokofiev; E. I. Ryabova; I. B. Esmagambetov; K. A. Pervoykina; E. A. Bogacheva; A. A. Lysenko; et al. (Тонкие химические технологии)
Objectives. To develop a technology for obtaining recombinant antibodies in a suspension culture of human HEK293 cells using transduction with recombinant adenovirus serotype 5 (rAd5) carrying genes expressing heavy and light chains of antibodies on the example of two broadspectrum anti-influenza antibodies 27F3 and CR9114.Methods. Ad5-27F3-H, Ad5-CR9114-H, and Ad5-27F3-L recombinant adenoviruses carrying the 27F3 antibody heavy chain gene, CR9114 antibody heavy chain gene, and 27F3 light chain gene, respectively, were generated using the AdEasy™ Adenoviral vector system. To accumulate preparative amounts of recombinant r27F3 and rCR9114 antibodies, the HEK293 suspension cell line was transduced with recombinant adenoviruses carrying genes for heavy and light chains of antibodies. The cells were cultured in a wave-type bioreactor. Chromatography was used to purify recombinant antibodies from the culture medium. After analyzing the molecular weights of purified antibodies using protein electrophoresis, their ability to interact with influenza A and B viruses was analyzed using the Western blot technique, while their ability to neutralize influenza A and B viruses was evaluated using the virus neutralization assay.Results. A method for the accumulation and purification of recombinant r27F3 and CR9114 antibodies from the culture medium of a suspension culture of human cells following transduction with its recombinant adenoviruses carrying the genes for heavy and light chains of these antibodies was developed. The ability of the r27F3 antibody to interact with and neutralize influenza A viruses of group 1 (except influenza A virus subtype H2) and group 2 was shown. The ability of the rCR9114 antibody to interact with influenza A viruses of group 1 and influenza B viruses, as well as to neutralize influenza A viruses of group 1, was demonstrated.Conclusions. A technology for obtaining recombinant antibodies in a suspension culture of HEK293 cells using transduction with recombinant adenoviruses carrying genes expressing heavy and light chains of antibodies was developed along with a confirmation of their specificity.